2009
DOI: 10.1016/j.crhy.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing acoustic measurements of the Boltzmann constant

Abstract: We review the progress in acoustic metrology of gases that has occurred since the 1988 measurement of the universal gas constant R using a spherical acoustic resonator. The advances in understanding resonators and in calculating the thermophysical properties of helium ab initio suggest that today one could determine Boltzmann's constant k B from acoustic measurements using either helium or argon with a relative uncertainty less than 10 −6 . RésuméProgrès dans la détermination de la constante de Boltzmann par v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The difference is the factor 2 in the denominator, which was omitted in [15] and in [35]. Additional corrections are generated by the two capillary tubes that carry gas into and out of the QSR.…”
Section: Acoustic Correction Modelmentioning
confidence: 99%
“…The difference is the factor 2 in the denominator, which was omitted in [15] and in [35]. Additional corrections are generated by the two capillary tubes that carry gas into and out of the QSR.…”
Section: Acoustic Correction Modelmentioning
confidence: 99%
“…We have not completed an analysis appropriate to the two-cylinder method; therefore, we now outline the complications and conclude by guessing the uncertainty contribution from fitting the data. First, we recall, that in the context of re-determining k B using argon in a quasispherical cavity resonator, one of us (MRM) observed that the lowest uncertainties can be obtained by measuring acoustic resonance frequencies in the range from 100 kPa to 500 kPa [20]. At still lower pressures, the perturbations from the thermo-acoustic boundary layer and the accommodation coefficients diverge; at higher pressures, the perturbations from the elastic response of the shell become excessive.…”
Section: Projected Uncertainty Budgetmentioning
confidence: 98%
“…In reference [20], one of us (MRM) estimated the relative uncertainties of the viscosity u r (η Ar ) ≈ 0.00025 and the thermal conductivity u r (λ Ar ) ≈ 0.00025 of argon in the limit of zero density at 273.16 K. Using these estimates in Eqs. 4 and 5 leads to an estimated relative uncertainty of the thermo-acoustic boundary layer correction: u r ( f b ) ≈ 0.00013.…”
Section: Accounting For the Larger Frequency Perturbationsmentioning
confidence: 99%
“…The best practical determination of F is by silver coulometry, and gives a relative uncertainty of 1.3 × 10 -6 [21,58,59], almost three orders of magnitude higher than u r (α 2 ). 10 The current value of R comes from direct measurements of the speed of sound in argon, and has u r = 1.7 × 10 -6 [21,58,60,61]: although there are ongoing efforts to measure k directly [62,63], rather than to determine it by k = R/N A (23) these have yet to reach the necessary precision even to supersede the value obtained from equation (22) [64,65]. 10 Indeed, ur(α 2 ) is more than an order of magnitude lower than the current relative uncertainties [44] in Ar( 14 In short, any additional reduction in the measurement uncertainty of fundamental constants by the redefinition of the mole in terms of a fixed numerical value of N A , over and above that achieved by fixing the numerical values of h, e and k, would be completely insignificant at the practical level.…”
Section: Quantum Metrology and Fundamental Constantsmentioning
confidence: 99%